Global Effects of Climate Change in the South China Sea and Its Surrounding Areas - Song Yang; Deliang Chen; Kaiqiang Deng (Ocean-Land-Atmosphere Research, 2024)
Climate change in the South China Sea and its surrounding areas (SCSSA), which include the Indo-Pacific Oceans, Southeast Asia, and the Tibetan Plateau, could exert profound impacts on both regional and global climate patterns. This study examines the unique characteristics of climate change in the SCSSA in the context of global warming, highlighting rapid warming in core areas, such as the Indo-Pacific Oceans and the Tibetan Plateau. The warming of the SCSSA has led to increased Asian summer monsoon precipitation, expanded Hadley circulation, an extended influence of the Madden–Julian Oscillation, and marked changes in tropical cyclone frequency and genesis location in the SCSSA. These changes in the Indo-Pacific Oceans and Tibetan Plateau affect not only downstream climates (East Asia, North America, Antarctica, and South America) through anomalous Rossby waves but also upstream regions (North Africa, South Europe, the North Atlantic, and the Middle East) by modulating atmospheric overturning circulations and Rossby wave patterns. This study also discusses the projected climate changes in the SCSSA under various future scenarios, indicating that the effects of future climate changes in the SCSSA on local and remote weather and climate extremes would be intensified. Understanding these dynamics is crucial for mitigating the consequences of climate change.